Band Structure Engineering in 2D Photonic Crystal Waveguide with Rhombic Cross-Section Elements. (12th May 2014) - Gharaati, Abdolrasoul; Zahraei, Sayed Hasan
Abstract : Two-dimensional photonic crystal (2D PhC) waveguides with square lattice composed of dielectric rhombic cross-section elements in air background, by using plane wave expansion (PWE) method, are investigated. In order to study the change of photonic band gap (PBG) by changing of elongation of elements, the band structure of the used structure is plotted. We observe that the size of the PBG changes by variation of elongation of elements, but there is no any change in the magnitude of defect modes. However, the used structure does not have any TE defect modes but it has TM defect mode for any angle of elongation. So, the used structure can be used as optical polarizer.